Effect of laser shock peening on the hot corrosion behavior of Ni-based single-crystal superalloy at 750°C. (June 2021) - Geng, Yongxiang; Mo, Yan; Zheng, Haizhong; Li, Guifa; Wang, Kedian
Highlights: Ni-based single-crystal (SC) superalloy was treated by laser shock peening (LSP). LSP induced different dislocation structures in both phases of the SC superalloy. Hot corrosion behavior of LSP treated Ni-based SC superalloy was studied. LSP enhanced the hot corrosion resistance of the SC superalloy. Hot corrosion products of the SC superalloy exhibited layered structures. Abstract: The hot corrosion behavior of a Ni-based single-crystal (SC) superalloy treated by laser shock peening (LSP) against 75 wt.% Na2 SO4 +25 wt.% NaCl molten salts at 750 °C was studied. The results showed that LSP improved the hot corrosion resistance of the SC superalloy. This was attributed to significantly different LSP-induced dislocation structures in γ/γ′ phases, which promoted the formation of protective layered oxide films that inhibited the inward diffusion of corrosive media. In addition, the hot corrosion mechanism of LSP-treated SC superalloy was discussed.